Akt regulates growth by directly phosphorylating Tsc2. - Potter, C.J.; Pedraza, L.G.; Xu, T. (Nature Cell Biology, 2002)
The direct mechanism by which the serine/threonine kinase Akt (also known as protein kinase B (PKB)) regulates cell growth is unknown. Here, we report that Drosophila melanogaster Akt/PKB stimulates growth by phosphorylating the tuberous sclerosis complex 2 (Tsc2) tumour suppressor and inhibiting formation of a Tsc1-Tsc2 complex. We show that Akt/PKB directly phosphorylates Drosophila Tsc2 in vitro at the conserved residues, Ser 924 and Thr 1518. Mutation of these sites renders Tsc2 insensitive to Akt/PKB signalling, increasing the stability of the Tsc1-Tsc2 complex within the cell. Stimulating Akt/PKB signalling in vivo markedly increases cell growth/size, disrupts the Tsc1-Tsc2 complex and disturbs the distinct subcellular localization of Tsc1 and Tsc2. Furthermore, all Akt/PKB growth signals are blocked by expression of a Tsc2 mutant lacking Akt phosphorylation sites. Thus, Tsc2 seems to be the critical target of Akt in mediating growth signals for the insulin signalling pathway.